Letter from Daniel D.L. Farson to Margaret M. Booth, May 15, 1888 - Farson, Daniel D. L. (1888)
Pennsylvania Horticultural Society Secretary, Daniel D. L. Farson writes to Margaret M. Booth née Cardeza with a memorial statement adopted by the Society in memory of her late husband, James Curtis Booth (1810-1888).
Keywords: Booth, James Curtis, 1810-1888; Pennsylvania Horticultural Society; Martinez Cardeza, Margaret